Advertising in the Dutch East Indies in Search of a Tropical Style - Maartje Brattinga (Wimba : Jurnal Komunikasi Visual, 2014)
This paper discusses advertising in Indonesia in the first half of the twentieth century. A period in which modern life started to emerge and when advertising professionalized. The Dutch colonizer was prominently involved in advertising and founded numerous advertising agencies. Dutch illustrators travelled to the Dutch East Indies to work as advertising artists. Under influence of the Indonesian arts and crafts, and the tropical surroundings they developed a specific Dutch-Indonesian style.